A method for toughening and strengthening asymmetric homoporous block polymer membranes

By immersing the block copolymer homoporous membrane into a solution containing an organic small molecule or polymer with a 1,2/1,3-dihydroxy structure, and crosslinking to form a gel coating, the problem of poor mechanical properties of the asymmetric homoporous membrane prepared by block copolymer is solved, and its fracture strength, elongation at break and toughness are significantly improved.

CN114225706BActive Publication Date: 2025-04-25ZHEJIANG UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202111338577.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-11-12
Publication Date
2025-04-25
Estimated Expiration
2041-11-12

Smart Images

  • Figure HDA0003351175680000011
    Figure HDA0003351175680000011
  • Figure HDA0003351175680000012
    Figure HDA0003351175680000012
  • Figure HDA0003351175680000013
    Figure HDA0003351175680000013
Patent Text Reader

Abstract

The present invention discloses a method for toughening and strengthening a block copolymer asymmetric homoporous membrane. The method mainly comprises the following steps: immersing the block copolymer homoporous membrane into a solution of an organic small molecule or polymer of a 1,2 / 1,3-dihydroxy structure, adjusting the pH value of the solution to fully infiltrate the membrane, adding a cross-linking agent and heating after taking it out, so that the cross-linking agent and the hydroxyl-containing polymer are cross-linked, and finally washing out the uncross-linked organic small molecules or polymers with water to obtain a block copolymer homoporous membrane containing a gel coating. The breaking strength increases by more than 20%, the elongation at break increases by more than 45%, and the toughness increases by more than 1.8 times. No fracture or structural damage will occur after moderate bending.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of membrane materials, and particularly relates to a method for toughening and strengthening an asymmetric isoporous block copolymer membrane. Background Art

[0002] The main challenge faced in membrane separation is that it is difficult to increase permeability and selectivity simultaneously. Uniform pore size and high pore density of uniform porous membranes have the potential to solve the permeability and selectivity trade-off effect due to their uniform pore size and high pore density. The current methods for preparing uniform porous membranes include anodization, core track etching, and block copolymer self-assembly, among which block copolymer self-assembly includes 1) selective removal; 2) selective swelling to form pores; 3) non-solvent induced phase separation (SNIPS). In contrast, SNIPS is simple to operate and the conditions are easy to control. It can produce a uniform porous surface with high pore density and an asymmetric structure with loose macropores (sponge-like / finger-like pores). It is the most promising technology for large-scale preparation of uniform porous membranes.

[0003] At the same time, the non-polar blocks of the block polymers used to prepare the homoporous membrane are mostly composed of polystyrene, which has a large incompatibility index χ with many polar blocks (poly-4-vinylpyridine, polyacrylic acid), and can be easily made into homoporous membranes. However, polystyrene is brittle and has poor mechanical properties, which makes the overall homoporous membrane show poor pressure resistance, poor toughness, and easy cracking, which seriously affects its practical application and large-scale preparation. Therefore, it is urgent to develop a method for enhancing and toughening the mechanical properties of polystyrene-based asymmetric homoporous membranes. Summary of the invention

[0004] In order to solve the above problems, the present invention proposes a method for toughening and strengthening a block polymer asymmetric homoporous membrane. The method is to immerse the block copolymer homoporous membrane into a solution containing small organic molecules or polymers with a 1,2 / 1,3-dihydroxy structure, and adjust the pH value of the solution so that the membrane is fully infiltrated, then take out the membrane, dry it and slightly heat it to produce crosslinking between the hydroxyl-containing substance and the crosslinking agent, and finally wash the membrane with water to wash out the uncrosslinked hydroxyl-containing substance to obtain a block copolymer homoporous membrane containing a gel coating. Compared with the original membrane, the homoporous membrane treated by this method has an increase in breaking strength of more than 20%, an increase in breaking elongation of more than 45%, and an increase in toughness of more than 1.8 times. No fracture or structural damage will occur after moderate bending. The defect of poor mechanical properties of the asymmetric homoporous membrane prepared from the original block copolymer is overcome.

[0005] The present invention adopts the following technical solution: a method for toughening and strengthening a block polymer asymmetric isoporous membrane, the method comprising the following steps:

[0006] (1) Immersing the block copolymer homoporous membrane into a solution containing a hydroxyl-containing substance; the hydroxyl-containing substance is a small molecule or polymer containing a 1,2 / 1,3-dihydroxy structure.

[0007] (2) Adjust the pH value of the solution to fully wet the membrane;

[0008] (3) taking out the membrane, immersing it in a solution containing a crosslinking agent (3-6 hours), taking it out and heating it to allow the crosslinking agent to crosslink with the hydroxyl-containing substance;

[0009] (4) washing and removing the uncrosslinked hydroxyl-containing substances to obtain a block copolymer homoporous membrane containing a gel coating.

[0010] Furthermore, the block copolymer asymmetric isoporous membrane has the following characteristics: the copolymer forming the isoporous membrane is composed of a polystyrene non-polar block and another polar block, wherein the polar block located in the pore is preferably a polymer containing carboxylic acid, pyridine, boric acid, hydroxyl, and ethylene glycol, including: polyacrylic acid, polymethacrylic acid, polytetravinylpyridine, polydivinylpyridine, polyhydroxyethyl methacrylate, polyethylene glycol, polyacrylamide phenylboric acid, and polytetravinylphenylboric acid.

[0011] Furthermore, the block copolymer asymmetric isoporous membrane has the following characteristics: the average pore size of the pores on its surface is not less than 5 nm, the pore size distribution is less than 25%, and the pore density is not less than 10 14 / m 2 ; The thickness of the support layer located below the surface uniformly porous layer is not less than 1 micron.

[0012] Furthermore, the cross-linking agent is preferably trimesaldehyde, glutaraldehyde, trimesoyl chloride, terephthaloyl diboric acid, and boric acid; and its concentration range is preferably 0.5wt% to 7.5wt%.

[0013] Furthermore, the small molecule or polymer of 1,2 / 1,3-dihydroxy structure is preferably composed of one or more of polyvinyl alcohol, hyaluronic acid, glucose, sucrose, chitosan, and maltose mixed in any proportion, and the number average molecular weight of the polymer is less than 5 kg / mol.

[0014] Furthermore, the concentration of the small molecules or polymers with 1,2 / 1,3-dihydroxy structure in step (1) is 10 g / L to 110 g / L.

[0015] Furthermore, in step (2), the pH value of the solution is adjusted to fully infiltrate the membrane, wherein the pH range is 5.5 to 9.5, preferably 7 to 9.5. The membrane infiltration time is 5 to 90 minutes, preferably 15 to 45 minutes.

[0016] Furthermore, in step (3), the heating temperature is 15-80° C., preferably 20-40° C. The heating time is greater than 0.5 hours, preferably 1.5 to 9 hours.

[0017] Furthermore, in the step (4), deionized water with a pH range of 5.9 to 7.4 is used to wash and remove the hydroxyl-containing substances that have not undergone cross-linking, and the washing method is immersion washing, and the washing time is 3-18 hours.

[0018] Furthermore, the toughened and reinforced block polymer asymmetric homoporous membrane has a fracture strength increased by more than 20%, a fracture elongation increased by more than 45%, a toughness increased by more than 1.8 times, a homoporous pore size reduction of less than 15%, and a water flux reduction of less than 25%.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] (1) The present invention provides a universal method for strengthening and toughening polystyrene-based block polymer asymmetric isoporous membranes;

[0021] (2) The present invention proposes a method for post-processing a homoporous membrane to achieve toughening and strengthening, which is particularly combined with the characteristics that the homoporous membrane has a hydrophilic environment in the pores, which makes it easy for the hydrophilic cross-linking agent to enter the pores and form a continuous gel coating in the pores;

[0022] (3) The present invention utilizes the asymmetric structure of the isoporous membrane, so that the gel coating is mainly loaded into the macropores of the support layer, which can significantly improve the mechanical strength of the membrane without significantly reducing the pore size or flux, thereby extending the service life of the isoporous membrane;

[0023] (4) The method provided by the present invention is simple and easy to implement, and the conditions are mild. It will not change the surface uniform pore structure of the asymmetric uniform pore membrane, and the uniform pore structure is well maintained after modification. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 : Scanning electron microscopy characterization of the surface of block copolymer asymmetric homoporous membrane;

[0025] Figure 2 : Fourier transform infrared spectra of asymmetric homoporous membrane before and after cross-linking;

[0026] Figure 3 : X-ray photoelectron spectra of asymmetric homogeneous porous membrane before (A) and after (B) cross-linking;

[0027] Figure 4 : The tensile properties test diagram of asymmetric uniform pore membrane before and after cross-linking;

[0028] Figure 5 : Scanning electron microscopy characterization of the front, back and cross-section of the asymmetric isoporous membrane before and after cross-linking. DETAILED DESCRIPTION

[0029] The present invention is further described below in conjunction with specific embodiments, but the described embodiments do not constitute a limitation of the present invention.

[0030] Example 1

[0031] 1) Preparation of block polymer asymmetric isoporous membrane: A polystyrene-block-polymethacrylic acid copolymer with a polymethacrylic acid polar block accounting for 20wt% and a block polymer number average molecular weight of 83kg / mol is dissolved in a mixed solvent of 1,4-dioxane and N,N-dimethylformamide (8:2, wt%:wt%) to form a casting solution. Among them, the mass fraction of the block polymer is 26wt%, and the mass fraction of the mixed solvent is 74wt%. The casting solution is stirred until the block polymer is completely dissolved to form a uniform and clear solution, and then allowed to stand for about 6h. Use a scraper with a thickness of 100μm to apply the casting solution to a clean glass plate, and after the solvent evaporates for 20s, transfer the glass plate to a coagulation bath filled with deionized water. After the solvent exchange is complete, the membrane is removed from the coagulation bath, and the surface morphology of the membrane is characterized by scanning electron microscopy, see attached. Figure 1 , the pore size is 15nm, the pore size distribution is 10%, and the pore density is 10 14 / m 2 of uniformly porous membrane.

[0032] 2) Post-film cross-linking modification: The prepared isoporous membrane was immersed in a 20 g / L polyvinyl alcohol solution, and the pH of the solution was adjusted to 7.0 to allow the membrane to be fully infiltrated for about 30 minutes. The membrane was fished out and placed in a 50°C oven for heating for about 3 hours. The membrane was then taken out and cross-linked using 5 wt% trimesaldehyde as a cross-linking agent. Finally, the membrane was washed with deionized water at a pH of 6.5 for about 10 hours to wash off the excess cross-linking agent on the surface. Fourier transform infrared spectroscopy was performed on the original membrane and the modified membrane. Figure 2 It is the Fourier transform infrared spectrometer characterization diagram of the asymmetric isoporous membrane prepared by block copolymer before and after crosslinking. The disappearance of the BOH characteristic peak indicates the successful crosslinking of the functional block in the membrane and the crosslinking agent, and a gel coating is formed in the macropores of the isoporous membrane support layer.

[0033] Figure 3 This is the X-ray photoelectron spectroscopy analysis of the asymmetric isoporous membrane prepared by block copolymer before and after crosslinking. The formation of BOC bonds indicates the successful formation of the crosslinking structure in the membrane.

[0034] 3) The tensile properties of the original film and the modified film were tested respectively. Figure 4It is a tensile performance test chart of the asymmetric uniform pore membrane before and after cross-linking. The stress-strain curve reflects that the toughness of the cross-linked membrane is significantly improved compared with the original membrane, which is about 4-5 times that of the original membrane, and the breaking strength is increased by more than 20%, and the elongation at break is increased by more than 45%.

[0035] Figure 5 The surface, back and cross-sectional morphologies of the modified membrane show that the surface morphology of the homoporous membrane has not changed significantly before and after cross-linking, indicating that the homoporous structure of the membrane surface will not be destroyed before and after cross-linking. Before cross-linking, the pore size is 15.0 nm, the pore size distribution is 10%, and the pore density is 10. 14 / m 2 At the same time, its cross-sectional diagram shows that the cross-section of the membrane becomes denser after cross-linking, and the pores are filled with gel. Among them, due to the presence of clearly structured finger-shaped macropores in the membrane sublayer, the finger-shaped pores have lower mass transfer resistance than sponge pores, so cross-linking agents and small molecules are more likely to enter the finger-shaped pores of the support layer and form a cross-linked structure filled with gel. The pore size of the membrane surface after cross-linking is 14.6nm, the pore size distribution is 12%, and the pore density is 10 14 / m 2 This ensures that the mechanical strength of the membrane is significantly improved without significantly reducing the pore size or the flux.

[0036] Example 2

[0037] 1) Preparation of block polymer asymmetric uniform porous membrane: A polystyrene-block-polyacrylamide phenylboric acid copolymer with a polyacrylamide phenylboric acid polar block accounting for 22wt% and a block polymer number average molecular weight of 76kg / mol is dissolved in a mixed solvent of 1,4-dioxane and N,N-dimethylacetamide (9:1, wt%:wt%) to form a casting solution. Among them, the mass fraction of the block polymer is 24wt%, and the mass fraction of the mixed solvent is 76wt%. The casting solution is stirred until the block polymer is completely dissolved to form a uniform and clear solution, and then allowed to stand for about 6h. Use a scraper with a thickness of 100μm to apply the casting solution to a clean glass plate, and after the solvent evaporates for 30s, transfer the glass plate to a coagulation bath filled with deionized water. After the solvent exchange is complete, the membrane is removed from the coagulation bath, and the surface morphology of the membrane is characterized by a scanning electron microscope, and the pore size is 13nm, the pore size distribution is 12%, and the pore density is 10 14 / m 2 of uniformly porous membrane.

[0038] 2) Cross-linking modification after film formation: The prepared isoporous membrane was immersed in a 10 g / L glucose solution, and the pH of the solution was adjusted to 8.5 to allow the membrane to be fully soaked for about 25 minutes. The membrane was fished out, placed in a 40°C oven for heating treatment for about 6 hours, and then taken out. Boric acid with a concentration of 3.5 wt% was used as a cross-linking agent to cross-link the membrane. Finally, the membrane was washed with deionized water with a pH of 7.0 for about 15 hours to wash away excess cross-linking agent on the surface. Fourier transform infrared spectroscopy and X-ray photoelectron spectroscopy were performed on the original membrane and the modified membrane, which showed that the cross-linking was successful and a gel coating was formed in the macropores of the isoporous membrane support layer.

[0039] 3) The original membrane and the modified membrane were subjected to tensile performance tests and membrane morphology analysis respectively. The results showed that the toughness of the cross-linked membrane was significantly improved compared with the original membrane without significantly reducing the pore size or flux.

[0040] Example 3

[0041] 1) Preparation of block polymer asymmetric isoporous membrane: A polystyrene-block-polyhydroxyethyl methacrylate copolymer with a polyhydroxyethyl methacrylate polar block accounting for 24wt% and a block polymer number average molecular weight of 91kg / mol was dissolved in a mixed solvent of 1,4-dioxane and N,N-dimethylformamide (8:2, wt%:wt%) to form a casting solution. Among them, the mass fraction of the block polymer is 28wt%, and the mass fraction of the mixed solvent is 72wt%. The casting solution is stirred until the block polymer is completely dissolved to form a uniform and clear solution, and then allowed to stand for about 6h. Use a scraper with a thickness of 100μm to apply the casting solution to a clean glass plate, and after the solvent evaporates for 15s, transfer the glass plate to a coagulation bath filled with deionized water. After the solvent exchange is complete, the membrane is removed from the coagulation bath, and the surface morphology of the membrane is characterized by a scanning electron microscope, and the pore size is 17nm, the pore size distribution is 11%, and the pore density is 10 14 / m 2 of uniformly porous membrane.

[0042] 2) Cross-linking modification after film formation: The prepared isoporous membrane is immersed in a 30 g / L sucrose solution, and the pH of the solution is adjusted to 7.0 to allow the membrane to be fully soaked for about 3 hours. The membrane is fished out, placed in a 30°C oven for heating treatment for about 8 hours, and then taken out. The membrane is cross-linked using 4.5 wt% terephthalic acid as a cross-linking agent. Finally, the membrane is washed with deionized water with a pH of 7.0 for about 18 hours to wash away excess cross-linking agent on the surface. The original membrane and the modified membrane are characterized by Fourier transform infrared spectroscopy and X-ray photoelectron spectroscopy, indicating that the cross-linking is successful and a gel coating is formed in the macropores of the isoporous membrane support layer.

[0043] 3) The original membrane and the modified membrane were subjected to tensile performance tests and membrane morphology analysis respectively. The results showed that the toughness of the cross-linked membrane was significantly improved compared with the original membrane without significantly reducing the pore size or flux.

[0044] Example 4

[0045] 1) Preparation of block polymer asymmetric isoporous membrane: A polystyrene-block-polytetravinylpyridine copolymer with a polytetravinylpyridine polar block accounting for 24wt% and a block polymer number average molecular weight of 75kg / mol is dissolved in 1,4-dioxane to form a casting solution. Among them, the mass fraction of the block polymer is 26wt%, and the mass fraction of the solvent is 74wt%. The casting solution is stirred until the block polymer is completely dissolved to form a uniform and clear solution, and then allowed to stand for about 6h. Use a scraper with a thickness of 100μm to apply the casting solution to a clean glass plate, and after the solvent evaporates for 25s, transfer the glass plate to a coagulation bath filled with deionized water. After the solvent exchange is complete, the membrane is removed from the coagulation bath, and the surface morphology of the membrane is characterized by scanning electron microscopy, and the pore size is 18nm, the pore size distribution is 13%, and the pore density is 10 14 / m 2 of uniformly porous membrane.

[0046] 2) Cross-linking modification after film formation: The prepared isoporous membrane is immersed in a 50 g / L maltose solution, and the pH of the solution is adjusted to 6.0 to allow the membrane to be fully soaked for about 15 minutes. The membrane is fished out, placed in a 35°C oven for heating treatment for about 6.5 hours, and taken out. The membrane is cross-linked using 2.5 wt% trimesoyl chloride as a cross-linking agent. Finally, the membrane is washed with deionized water at a pH of 7.0 for about 15 hours to wash away excess cross-linking agent on the surface. The original membrane and the modified membrane are characterized by Fourier transform infrared spectroscopy and X-ray photoelectron spectroscopy, indicating that the cross-linking is successful and a gel coating is formed in the macropores of the isoporous membrane support layer.

[0047] 3) The original membrane and the modified membrane were subjected to tensile performance tests and membrane morphology analysis respectively. The results showed that the toughness of the cross-linked membrane was significantly improved compared with the original membrane without significantly reducing the pore size or flux.

[0048] Example 5

[0049] 1) Preparation of block polymer asymmetric uniform porous membrane: A polystyrene-block-polydivinylpyridine copolymer with a polydivinylpyridine polar block accounting for 21wt% and a block polymer number average molecular weight of 59kg / mol is dissolved in 1,4-dioxane to form a casting solution. Among them, the mass fraction of the block polymer is 25wt%, and the mass fraction of the solvent is 75wt%. The casting solution is stirred until the block polymer is completely dissolved to form a uniform and clear solution, and then allowed to stand for about 6h. Use a scraper with a thickness of 100μm to apply the casting solution to a clean glass plate, and after the solvent evaporates for 10s, transfer the glass plate to a coagulation bath filled with deionized water. After the solvent exchange is complete, the membrane is removed from the coagulation bath, and the surface morphology of the membrane is characterized by scanning electron microscopy, and the pore size is 15nm, the pore size distribution is 10%, and the pore density is 10 14 / m 2 of uniformly porous membrane.

[0050] 2) Cross-linking modification after film formation: The prepared isoporous membrane is immersed in 40 g / L chitosan solution, and the pH of the solution is adjusted to 8.0 to allow the membrane to be fully soaked for about 30 minutes. The membrane is fished out, placed in a 45°C oven for heating treatment for about 4 hours, and then taken out. 5 wt% glutaraldehyde is used as a cross-linking agent to cross-link the membrane. Finally, the membrane is washed with deionized water with a pH of 7.0 for about 10 hours to wash away excess cross-linking agent on the surface. The original membrane and the modified membrane are characterized by Fourier transform infrared spectroscopy and X-ray photoelectron spectroscopy, indicating that the cross-linking is successful and a gel coating is formed in the macropores of the isoporous membrane support layer.

[0051] 3) The original membrane and the modified membrane were subjected to tensile performance tests and membrane morphology analysis respectively. The results showed that the toughness of the cross-linked membrane was significantly improved compared with the original membrane without significantly reducing the pore size or flux.

[0052] Example 6

[0053] 1) Preparation of block polymer asymmetric uniform porous membrane: A polystyrene-block-poly-4-vinylbenzene boronic acid copolymer with a poly-4-vinylbenzene boronic acid polar block accounting for 19wt% and a block polymer number average molecular weight of 68kg / mol was dissolved in a mixed solvent of 1,4-dioxane and N,N-dimethylacetamide (9:1, wt%:wt%) to form a casting solution. Among them, the mass fraction of the block polymer is 26wt%, and the mass fraction of the mixed solvent is 74wt%. The casting solution is stirred until the block polymer is completely dissolved to form a uniform and clear solution, and then allowed to stand for about 6h. Use a scraper with a thickness of 100μm to apply the casting solution to a clean glass plate, and after the solvent evaporates for 20s, transfer the glass plate to a coagulation bath filled with deionized water. After the solvent exchange is complete, the membrane is removed from the coagulation bath, and the surface morphology of the membrane is characterized by scanning electron microscopy, and the pore size is 12nm, the pore size distribution is 13%, and the pore density is 1014 / m 2 of uniformly porous membrane.

[0054] 2) Cross-linking modification after film formation: The prepared isoporous membrane is immersed in a 100 g / L hyaluronic acid solution, and the pH of the solution is adjusted to 7.5 to allow the membrane to be fully soaked for about 3 hours. The membrane is fished out, placed in a 30°C oven for heating treatment for about 7 hours, and then taken out. The membrane is cross-linked using 7wt% of trimesaldehyde as a cross-linking agent. Finally, the membrane is washed with deionized water with a pH of 7.0 for about 8 hours to wash away excess cross-linking agent on the surface. The original membrane and the modified membrane are characterized by Fourier transform infrared spectroscopy and X-ray photoelectron spectroscopy, indicating that the cross-linking is successful and a gel coating is formed in the macropores of the isoporous membrane support layer.

[0055] 3) The original membrane and the modified membrane were subjected to tensile performance tests and membrane morphology analysis respectively. The results showed that the toughness of the cross-linked membrane was significantly improved compared with the original membrane without significantly reducing the pore size or flux.

[0056] Example 7

[0057] 1) Preparation of block polymer asymmetric uniform porous membrane: A polystyrene-block-polyethylene glycol copolymer with a polyethylene glycol polar block accounting for 22wt% and a block polymer number average molecular weight of 90kg / mol is dissolved in a mixed solvent of 1,4-dioxane and N,N-dimethylacetamide (9:1, wt%:wt%) to form a casting solution. Among them, the mass fraction of the block polymer is 25wt%, and the mass fraction of the mixed solvent is 75wt%. The casting solution is stirred until the block polymer is completely dissolved to form a uniform and clear solution, and then allowed to stand for about 6 hours. Use a scraper with a thickness of 100μm to apply the casting solution to a clean glass plate, and after the solvent evaporates for 20s, transfer the glass plate to a coagulation bath filled with deionized water. After the solvent exchange is complete, the membrane is removed from the coagulation bath, and the surface morphology of the membrane is characterized by scanning electron microscopy, and the pore size is 14nm, the pore size distribution is 8%, and the pore density is 10 14 / m 2 of uniformly porous membrane.

[0058] 2) Cross-linking modification after film formation: The prepared isoporous membrane is immersed in 80 g / L glucose solution, and the pH of the solution is adjusted to 6.5 to allow the membrane to be fully soaked for about 20 minutes. The membrane is fished out, placed in a 40°C oven for heating treatment for about 7.5 hours, and then taken out. Boric acid with a concentration of 5.5 wt% is used as a cross-linking agent to cross-link the membrane. Finally, the membrane is washed with deionized water with a pH of 7.2 for about 10 hours to wash away excess cross-linking agent on the surface. The original membrane and the modified membrane are characterized by Fourier transform infrared spectroscopy and X-ray photoelectron spectroscopy, indicating that the cross-linking is successful and a gel coating is formed in the macropores of the isoporous membrane support layer.

[0059] 3) The original membrane and the modified membrane were subjected to tensile performance tests and membrane morphology analysis respectively. The results showed that the toughness of the cross-linked membrane was significantly improved compared with the original membrane without significantly reducing the pore size or flux.

[0060] Example 8

[0061] 1) Preparation of block polymer asymmetric uniform porous membrane: A polystyrene-block-polyacrylic acid copolymer with a polyacrylic acid polar block accounting for 18wt% and a block polymer number average molecular weight of 59kg / mol is dissolved in a mixed solvent of 1,4-dioxane and N,N-dimethylformamide (9:1, wt%:wt%) to form a casting solution. Among them, the mass fraction of the block polymer is 24wt%, and the mass fraction of the mixed solvent is 76wt%. The casting solution is stirred until the block polymer is completely dissolved to form a uniform and clear solution, and then allowed to stand for about 6h. Use a scraper with a thickness of 100μm to apply the casting solution to a clean glass plate, and after the solvent evaporates for 20s, transfer the glass plate to a coagulation bath filled with deionized water. After the solvent exchange is complete, the membrane is removed from the coagulation bath, and the surface morphology of the membrane is characterized by scanning electron microscopy, and the pore size is 14nm, the pore size distribution is 8%, and the pore density is 10 14 / m 2 of uniformly porous membrane.

[0062] 2) Cross-linking modification after film formation: The prepared isoporous membrane was immersed in 45 g / L chitosan solution, and the pH of the solution was adjusted to 5.5 to allow the membrane to be fully soaked for about 10 minutes. The membrane was fished out, placed in a 45°C oven for heating treatment for about 5 hours, and then taken out. The membrane was cross-linked using 5 wt% of trimesaldehyde as a cross-linking agent. Finally, the membrane was washed with deionized water with a pH of 7.0 for about 13 hours to wash away excess cross-linking agent on the surface. The original membrane and the modified membrane were characterized by Fourier transform infrared spectroscopy and X-ray photoelectron spectroscopy, indicating that the cross-linking was successful and a gel coating was formed in the macropores of the isoporous membrane support layer.

[0063] 3) The original membrane and the modified membrane were subjected to tensile performance tests and membrane morphology analysis respectively. The results showed that the toughness of the cross-linked membrane was significantly improved compared with the original membrane without significantly reducing the pore size or flux.

[0064] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the present invention.

Claims

1. A method for toughening and strengthening asymmetric homoporous block copolymer membranes, characterized in that: The method comprises the following steps: (1) Immersing the block copolymer homoporous membrane in a solution containing a hydroxyl-containing substance; the hydroxyl-containing substance is a small molecule or polymer containing a 1,2 / 1,3-dihydroxy structure; the block copolymer homoporous membrane is made of a copolymer composed of a polystyrene non-polar block and another polar block, wherein the polar block located in the pore is a polymer containing carboxylic acid, pyridine, boric acid, hydroxyl, and ethylene glycol, including: polyacrylic acid, polymethacrylic acid, polytetravinylpyridine, polydivinylpyridine, polyhydroxyethyl methacrylate, polyethylene glycol, polyacrylamide phenylboric acid, polytetravinylphenylboric acid; the small molecule or polymer with a 1,2 / 1,3-dihydroxy structure is: one or more of polyvinyl alcohol, hyaluronic acid, glucose, sucrose, chitosan, and maltose mixed in any proportion, and the molar mass of the polymer is less than 5 kg / mol; the pore size of the average pore on the surface of the block copolymer homoporous membrane is not less than 5 nm, the pore size distribution is less than 25%, and the pore density is not less than 10 14 / m 2 ; The thickness of the support layer below the surface uniformly porous layer is not less than 1 micron; The concentration of the small molecule or polymer with 1,2 / 1,3-dihydroxy structure is 10 g / L~110 g / L; (2) Adjust the pH value of the solution to ensure that the membrane is fully infiltrated; (3) taking out the membrane, adding a cross-linking agent and heating to allow the cross-linking agent to cross-link with the hydroxyl-containing substance; the cross-linking agent is a mixture of one or more of trimesaldehyde, glutaraldehyde, trimesoyl chloride, terephthalic acid, and boric acid in any proportion; the concentration of the cross-linking agent is 0.5 wt% to 7.5 wt%; (4) The uncross-linked hydroxyl-containing substances are removed by washing to obtain a block copolymer homoporous membrane containing a gel coating.

2. The method according to claim 1, characterized in that In step (2), the pH value of the solution is adjusted to allow the membrane to be fully infiltrated, wherein the pH range is 5.5-9.5 and the membrane infiltration time is 5-40 min.

3. The method according to claim 1, characterized in that In the step (3), the heating temperature is 15-80°C and the heating time is greater than 0.5 hour.

4. The method according to claim 1, characterized in that: In the step (4), deionized water with a pH range of 5.9 to 7.4 is used to wash and remove the hydroxyl-containing substances that have not undergone cross-linking. The washing method is immersion washing, and the washing time is 3 to 18 hours.

5. The method according to claim 1, characterized in that The block copolymer homoporous membrane containing a gel coating obtained in step (4) has a breaking strength increased by more than 20%, a breaking elongation increased by more than 45%, a toughness increased by more than 1.8 times, a reduction in the homoporous pore size of less than 15%, and a reduction in the water flux of the homoporous membrane of less than 25%.

Citation Information

Patent Citations

  • Separation membrane and preparation method thereof

    CN109248569A

  • Isoporous membranes including crosslinked multiblock copolymers

    CN112423868A